The impact of food price changes and land policy reforms on household welfare in rural Tanzania - Tukae Mbegalo (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2016)
Land policy reforms across Africa are expected to address several of the underlying critical issues of food security and economic development, because they can help stabilize food prices by improving future expectations on trade and supply. However, there is an absence of solid empirical research that considers the relationship between food price and land policy reform. This paper simultaneously estimates the impact of food prices and the Land Act of 1999 on rural household welfare. We use panel data from 2008/2009 and 2010/2011. The data contains information on land ownership and the different forms of land titling. This allows us to construct a treatment variable for landownership before and after the Land Act. Then, we use a matching method to estimate the counterfactual effect of both net consumer and producer welfare. The results indicate that rural food producers have not benefited by the post independence land reforms. Furthermore, we found that education and land titling have a major influence on improving household welfare as well as in offsetting food price shocks and reducing rural food poverty. We argue that education attainment can facilitate literacy on land and credit market issues, enabling the rural population to take full advantage of land titling, which can be used as collateral. Finally, we found that although land titling is an important tool in reducing rural food poverty, few poor rural households have land use certification. This is a crucial issue because titling and access to land for the rural poor are essential for food security and rural economic development.
Keywords: 330; Food Price; Education; Household Welfare; Land Ownership; Land Act; Land Titling and Matching Methods